Effects of Surfactants on Biological, Physiological, and Histological Performance of Mahseer Seeds, Neolissochilus soro - Rizkiya, Iffi; Juliandi, Berry; Nirmala, Kukuh; Puspaningsih, Dewi; Taufik, Imam (Bogor Agricultural University, Indonesia, 2024)
Mahseer (Neolissochilus soro) grows and develops in Indonesian lakes and rivers. However, in line with the increase in population, the pollution load that enters water bodies is increasing due to anthropogenic activities along the river. One of the chemicals that can potentially be a source of water pollution is Linear Alkylbenzene Sulfonate (LAS). This study aims to determine the lethal toxicity of LAS surfactant to mahseer and to analyze the sub-lethal effect of this surfactant on the biological, physiological, and histological conditions of mahseer seeds. Parameters studied included lethal toxicity (LC50), sub-lethal toxicity, and biological, histological, and hematological conditions. The results showed that the LAS surfactant had an LC50-96 hour value of 6.14 mg/L in mahseer and was classified as highly toxic. Fish exposed to LAS for 40 days experienced a decrease in specific growth rate and feed efficiency as the surfactant concentration increased. Exposure to LAS also decreases the number of erythrocytes, hemoglobin, hematocrit, and blood sugar levels while increasing the number of leukocytes. There was also damage to the gills of fish exposed to LAS. In general, the sub-lethal concentration of LAS negatively affected mahseer seeds.